Complete mitochondrial genome of the Chinese skipper, Polytremis jigongi (Lepidoptera: Hesperiidae). (3rd July 2016) - Yang, Qichang; Zhao, Huidong; Chang, Yuan; Liu, Lu; Zhu, Jianqing; Yu, Weidong; Jiang, Weibin
Abstract: The sequence of the mitochondrial genome (mitogenome) of Polytremis jigongi (Lepidoptera: Hesperiidae) has been presented in this article. It is 15, 353 bp in length, with an A + T content of 80.9% containing 13 protein-coding genes, 22 tRNAs, 2 rRNAs, and a noncoding control region (D-loop). All of the 37 typical animal mitochondrial genes were found. All protein-coding genes started with ATN as a start codon except for the gene COX1 that uses CGA as in other lepidopteran species. Five protein-coding genes use incomplete stop codon TA or T, while the others use TAA as stop codons. Most of the tRNA genes can be folded into a typical cloverleaf structure. Nucleotide composition is similar to other insects, showing a high bias toward A + T. Phylogenetic analysis showed that the genome sequence of P. jigongi is close to Hesperiidae.